Identification of potential miRNA-mRNA regulatory network and the key miRNAs in intramuscular and subcutaneous adipose - Feng, Hui; Liu, Tianyi; Yousuf, Salsabeel; Zhang, Xiuxiu; Huang, Wanlong; Li, Ai; Xie, Lingli; Miao, Xiangyang (Frontiers in Veterinary Science, 2022)
Intramuscular fat (IMF) is an important indicator for evaluating meat quality. Breeds with high IMF content are often accompanied by high subcutaneous fat (SCF)， severely affecting the meat rate of pigs. It is of great significance for porcine breeding to explore the mechanism of miRNA which is related to adipogenesis and lipid metabolism. We constructed two small RNA libraries from intramuscular and subcutaneous fat to evaluate the patterns of lipogenesis in Laiwu pig, a Chinese breed. A total of 286 differentially expressed miRNAs (DEmiRNAs), including 193 known miRNA and 93 novel miRNAs, were identified from two types of adipose. GO and KEGG enrichment analysis for DEmiRNAs showed that their target genes involved in many adipogenesis and lipid metabolism biological processes and signaling pathways, such as Wnt signaling pathway，MAPK signaling pathway, Hippo signaling pathway, PI3K-Akt signaling pathway, Melanogenesis, Signaling pathways regulating pluripotency of stem cells and so on. Then, we constructed a miRNA-mRNA interaction network to find out which miRNAs were the key miRNAs of regulation in Wnt signaling pathway. In this pathway, miR-331-3p, miR-339-5p, miR-874 and novel346_mature target PPARD, WNT10B, RSPO3, WNT2B. This study provides a theoretical basis for further understanding the post-transcriptional regulation mechanism of meat quality formation and predicting and treating diseases caused by ectopic fat.